Fundamentals of Entrepreneurship (ENT300) Grilled House / Hezran Syamer Hattono... [et.al] - Hattono, Hezran Syamer; Abdul Rahman, Abdul Rafi Rahimi; Rosli, Muhammad Afiq Aiman; Dahlan, Amirul Haziq (2017)
The name of our company is Grilled House where we selling variety types of grill food and beverages. The nature of business for our company is partnership. Our business was located at Taman Boulevard Jalan Setiaraja 964A0 Mukah, Sarawak. We would like to take the opportunity to start up this business due to less number of competitors in that area. The future prospects of our business is where we want to create a good relationship with our customer. Each partner of this business will contributes RM9829 for the business. Next, for administration manager, our business consists of general manager, administration manager, marketing manager, operational manager and financial manager. We also provide compensation and benefits for our business such as Social Safety policy(SOCSO), Employees Provident Fund(EPF), working days and emergency leave. For our marketing manager which is Abdul Rafi Rahimi Bin Abdul Rahman, he will responsible to create a marketing plan for our business, search a location that is strategic to open our business and analyzing the competitors. Not only that, he also will analyze the market size, the market share, market strategy and forecasting our sales. The operation manager of our business will be focus on the operation part which is managed by Mr. Muhammad Afiq Aiman Bin Rosli. He will be responsible to ensure the business operation system run smoothly in order to maintain the quality of the products and services to customers, He also responsible for the job that related to the admin roles such as arranging the remuneration and t}le wages of the employees. Lastly, the financial manager will be Amirul Haziq Bin Dahlan and he will be responsible in financial roles of our company. Financial plan is crucial to the overall business plan that is developed for a particular business or project, it is importance because to determine the size of investment , to identify and propose the relevant source of finance and to ensure that the initial capital is sufficient. Next the roles of financial manager is to handle the financial plan as preparing the budget and financial statement for expenses and profit or loss of our business.